A Design, Molecular Docking, ADMET Studies, Synthesis, Characterization, and Invitro Pharmacological Evaluation of Tetrazole Derivatives - Sager, Athra; Ferman Abbood, Ammar; Jawad Kadhim Abaies; Abbas Khazal, Fatma (Iraqi Journal of Pharmaceutical Sciences, 2025)
A series of novel tetrazole derivatives were designed and synthesized through ring closure. The structures of compounds (T1-T9) were characterized by FT-IR, 1H, and 13C-NMR spectroscopy. All tetrazole derivatives were screened for their antimicrobial activities against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria. All compounds showed a high activitiy against E. coli at a concentration of 0.01 mg/mL, while the tested compound T2 did not exhibit remarkable activity against Gram-positive Staphylococcus aureus. The potential DNA gyrase inhibitory activity of these compounds ( T1-T9 ) was investigated by Insilico using the molecular docking simulation method. All compounds showed good results, especially compound (T8), which showed the lowest binding affinity (-8.8 Kcal/mol).